Pareto front analysis method for optimization of PV inverter based volt/var control considering inverter lifetime - Chai, Qingmian (2023)
Photovoltaic (PV) inverter-based volt/var control (VVC) is highly promising to tackle the emerging voltage regulation challenges brought by increasing PV penetration. However, PV inverter operational reliability has arisen as a critical concern for practical VVC implementation. This paper proposes a new PV inverter based VVC optimization model and a Pareto front analysis method for maintaining a satisfactory inverter lifetime. First, reliability of the vulnerable DC-link capacitor inside a PV inverter is analyzed, and long-term VVC impact on inverter operational reliability is identified. Second, a multi-objective PV inverter based VVC optimization model is proposed for minimizing both inverter apparent power output and network power loss with a weighting factor. Third, a Pareto front analysis method is developed to visualize the impact of the weighting factor on VVC performance and inverter reliability, thus determining the effective weighting factor to reduce network power loss with expected inverter lifetime. Effectiveness of the proposed VVC optimization model and Pareto front analysis method are verified in a case study.